2011
DOI: 10.1080/00220388.2010.492857
|View full text |Cite
|
Sign up to set email alerts
|

Financial Access and Exclusion in Kenya and Uganda

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 31 publications
(31 reference statements)
4
67
1
1
Order By: Relevance
“…Indeed, Porteous terms mobile-based services those that are targeted to the unbanked and offer new channels of access, "transformational" (Porteous 2006). In this context, we ask whether these new developments indeed represent a transformational shift in the Kenyan market and whether there is evidence that this expansion is overcoming barriers to access previously evident in Kenya such that characteristics previously associated with the unbanked such as employment, gender, age, education and location (Johnson and Niño-Zarazua 2011) are in fact changing.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Porteous terms mobile-based services those that are targeted to the unbanked and offer new channels of access, "transformational" (Porteous 2006). In this context, we ask whether these new developments indeed represent a transformational shift in the Kenyan market and whether there is evidence that this expansion is overcoming barriers to access previously evident in Kenya such that characteristics previously associated with the unbanked such as employment, gender, age, education and location (Johnson and Niño-Zarazua 2011) are in fact changing.…”
Section: Introductionmentioning
confidence: 99%
“…29 The fact that groups are usually composed mostly of women helps reduce the gender gap in the use of both formal and informal finance. See Johnson and Nino-Zarazua (2011). 30 The details about the Mali program, the study methodology and the detailed results are found in Beaman et al (2014).…”
mentioning
confidence: 99%
“…Gender-neutral regulations can result in gender-sensitive outcomes (Johnson andNinoZarazua, 2011). Cull et al (2011) show that profit-oriented MFIs respond to supervision by serving fewer women in order to maintain profit rates.…”
Section: Resultsmentioning
confidence: 99%